AVALIAÇÃO DO CONFORTO TÉRMICO NO EDIFÍCIO V2 DA UNIVERSIDADE DE PASSO FUNDO - Frandoloso, Marcos Antonio Leite; Bier, Angelica; Mainardi, Matheus Scaglia; Mazieiro, Bruna; Spader, Julia de Freitas; Tomasi, Sabrina; Pinto, Fábio Lamaison; Rebelatto, Bianca Gasparetto; Azevedo, Melissa Alencar (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The thermal comfort in a building is important for the well-being of the user and for the good performance of the activities developed within the built environment. Therefore, it's necessary to maintain appropriate levels of temperature and relative humidity to ensure energy efficiency, and then to minimize the use of active thermal conditioning systems. The study object is part of a research project developed at Universidade de Passo Fundo - UPF, and it has as element of analysis the V2 building. Concomitantly with the occupation of the building in 2015, the analyses verify the thermal conditions of the classrooms through the variables of dry bulb temperature and relative humidity through Data-Loggers. The data obtained from the internal measurements allowed a compilation of time and seasonal diagrams. Also, the information was analysed based on the characteristics and the performance of the building envelope. In this way, it was observed that the thermal sensations of the internal environments, considering the climatic complexity of Passo Fundo, indicate periods of discomfort. Based on the data diagnosis, improvements in the university spaces are being sought, to reach a better academic performance within the structure under analysis, as well as the whole building stock.